2016
DOI: 10.1126/sciadv.1600224
|View full text |Cite
|
Sign up to set email alerts
|

Targeting macrophage necroptosis for therapeutic and diagnostic interventions in atherosclerosis

Abstract: Necroptosis promotes necrotic core and vulnerable atherosclerosis in humans and mice and is a prospective therapeutic and diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
244
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(261 citation statements)
references
References 51 publications
9
244
2
6
Order By: Relevance
“…Earlier reports indicate that, NF-kB inhibition is known to reduce necroptosis and formation of inflammasomes [68][69][70][71]. It is notable in this regard that, Karunkaran et al state, i.e., "necroptic cell death is activated in human advanced atherosclerotic plaques" [79], fits in well with our findings. Their studies have shown that, macrophages residing within the plaques were increased in RIPK3 concentration.…”
supporting
confidence: 93%
“…Earlier reports indicate that, NF-kB inhibition is known to reduce necroptosis and formation of inflammasomes [68][69][70][71]. It is notable in this regard that, Karunkaran et al state, i.e., "necroptic cell death is activated in human advanced atherosclerotic plaques" [79], fits in well with our findings. Their studies have shown that, macrophages residing within the plaques were increased in RIPK3 concentration.…”
supporting
confidence: 93%
“…Progression to plaque necrosis is a key process because of the highly inflammatory and plaque-destabilizing nature of the necrotic core (26). Data from human and mouse studies suggest that plaque necrosis results from 2 complementary processes, postapoptotic necrosis secondary to defective efferocytosis as examined here (2, 3) and a primary cell necrosis process called necroptosis (27,28). While the current study is focused on an efferocytosis defect in phagocytes themselves, a recent study showed that some apoptotic cells in human and mouse lesions inappropriately retain CD47, which blocks their engulfment by normal phagocytes (29).…”
Section: Resultsmentioning
confidence: 80%
“…internalized by normal phagocytes (28). Defects in multiple steps of efferocytosis, together with activation of necroptotic pathways in advanced plaques, would create a "perfect storm" for the development of plaque necrosis.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Once infiltrated into the subendothelial space, some immune cells will unlimitedly take up lipids to continuously enlarge plaque [21]. The death of macrophage could induce plaque necrosis in advanced plaques, which may result in plaques instability and thus cause plaque rupture.…”
Section: Let-7g and Inflammationmentioning
confidence: 99%
“…The death of macrophage could induce plaque necrosis in advanced plaques, which may result in plaques instability and thus cause plaque rupture. Therefore, strategies to prevent macrophages apoptosis may stabilize the vulnerable plaques and reduce the life-threatening complications [21]. In addition, the interplays among immune cells, endothelial cells, platelets and smooth muscle cells facilitate the progres-sion of the atherosclerotic plaques [22] [23].…”
Section: Let-7g and Inflammationmentioning
confidence: 99%